Trust, foundation and waqf development: emerging of established traditions - Syed Abdul Kader, Sharifah Zubaidah (2015)
This paper examines the evolution and development of the trust, foundation and waqf concepts from the legal historical perspective and looks at how these concepts are being used in present times.